Fractional abdunances of plant taxa in the Tajik-Uzbek Surface Data Base - Lucas Dugerdil; Odile Peyron; Guillemette Ménot; Dilfuza Egamberdieva; Jakhongir Alimov; Suzanne A G Leroy; Eric Garnier; Arkadiusz Nowak; Sébastien Joannin (PANGAEA, 2025)
This dataset contains the fractional abundances of each plant taxon from the vegetations plots of the TUSDB. The fractional abundances are expressed in %. The plant taxa are given at the most accurate level of identification (i.e. species when possible, genus or family otherwise).
In: Dugerdil, L et al. (2025): Tajik-Uzbek Surface Data Base for modern pollen samples and vegetation plots: calibrations for functional diversity, climate and vegetation reconstructions in the past [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.979582